The Emergence of Crowdinvesting in Europe - Lars Hornuf; Armin Schwienbacher (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
This paper first presents the development of the crowdinvesting market in Europe since its start in 2007. Then, using hand-collected data on the complete set of crowdinvesting campaigns run in Germany, the paper shows that successful campaigns tend to be launched by new startups and when the minimum ticket size is small so that more crowd investors can participate. Moreover, the use of the partiarisches Darlehen (a specific form of equity-linked notes not subject to prospectus regulation) adopted at the end of 2012 in Germany (as a response to alleviating regulatory constraints) has led to larger amounts being raised but also campaigns becoming more likely to achieve their targets. These two results combined indicate that contractual arrangements that enable more participation from the crowd tend to work best. Finally, campaigns launched on portals already having some experience are more likely to raise larger amounts. These findings should be of use to entrepreneurs who need to choose among a larger range of different crowdinvesting portals.
urn:nbn:de:bvb:19-epub-21388-8
Keywords: G3; L26; M13; K22; 330; entrepreneurial finance; business finance; crowdinvesting; equity crowdfunding